AWARENESS OF RISK FACTORS ASSESSMENT AMONG INDIVIDUALS WITH ISCHEMIC HEART DISEASE - Franek, Grażyna; Ćmiel-Giergielewicz, Marta; Nowak-Kapusta, Zofia; Zmysło-Rogozik, Marzena (Medical and Biological Sciences, 2012)
Aim. Awareness of risk factors assessment concerning preventive measures to an ischemic heart disease depending on socio-demographical factors such as: age, sex, education, place of residence and financial situation among hospitalised individuals. Introduction. The ischemic heart disease is the most frequent cause of death, hospitalisation and disability. The increasing number of the individuals suffering from the disease underlines the importance of taking preventive measures among the whole population. Proper health education and addressing the risk factors are one of the more crucial parts of preventing the ischemic heart disease. Material and method. A method of a diagnostic questionnaire along with the survey technique was used in the work; an anonymous research was done among 101 individuals with ischemic heart disease. The individuals were hospitalised in the Preventive Diagnostics and Telemedicine of Heart and Lungs Conditions of the John Paul II Hospital in Krakow. The questionnaire contained 47 questions concerning the awareness of preventive measures to ischemic heart disease and its use in everyday life. Results. The obtained results pointed to the lack of awareness among patients and their awareness of risk factors. The researched individuals were not aware of all the factors, did not know how to modify the risks in order not to develop the ischemic heart disease. The obtained results revealed that the higher the education, the improved the knowledge of the risk factors of ischemic heart disease (58.1% of correct answers). The results also showed that sex was the differentiating factor in the knowledge about the condition. Only 33% of the individuals were educated on the ways of modifying the risk factors of the heart disease. Conclusions. The data from the research point to the lack of education among patients with ischemic heart condition as well as the necessity to address the preventive measures according to the education, sex and the age of patients.